Gastric cell c-AMP stimulating autoantibodies in duodenal ulcer disease. Issue 1 (January 1988) - De Lazzari, F; Mirakian, R; Hammond, L; Venturi, C; Naccarato, R; Bottazzo, G F
Abstract : Gastric cell c-AMP stimulating antibodies (GCS-Ab) were studied in 30 patients with duodenal ulcer (DU) disease. Semipurified immunoglobulin (Ig) preparations from 13/30 patients stimulated c-AMP production in parietal cell enriched gastric cell suspensions obtained from male guinea pig stomachs. Maximum stimulation (varying between 260 and 547%) was reached after four hours incubation with 2 and 4 mg/ml Ig concentrations. The 13 patients with gastric cell stimulating antibodies (GCS-Ab), all male patients, developed the disease at a younger age (nine of 13 under the age of 30), had a longer duration of symptoms (mean 18.4 years), and had a higher incidence of DU in their families (61%). Eight of 13 (61%) in the GCS-Ab+ group did not respond to anti-H2-R drugs, whereas in the negative patients only three of 17 (18%) were classified as 'non-responders'. Remarkably few conventional autoantibodies were detected in our series. Gastric cell stimulating antibodies are a new addition to the growing list of receptor antibodies in human diseases and the described in vitro test should provide an easier tool for screening large populations.